Design and Validation of the Brief Self Online Scale (SO-8) in Early Adolescence: An Exploratory Study - Ortega-Barón, Jessica; Machimbarrena, Juan Manuel; Montiel, Irene; Buelga, Sofía; Basterra-González, Mª Aránzazu; González-Cabrera, Joaquín (Journal of early adolescence, 2021)
For the Z-Generation, the Internet has become a very important experimentation laboratory for the discovery and validation of their identity. Despite the importance of the process of building the self in the adolescent, there are hardly any validated instruments that measure the self online. The aim of this research was to design and validate the Brief Self Online Scale (SO-8). A total of 843 students (384 boys, 45.6%), with an age range of 10 to 14 years participated. Confirmatory factor analysis (CFA) confirmed the hypothesized model of two correlated factors (Online Self-Perception and Online Idealized Projection), previously obtained through exploratory factor analysis (EFA). The reliability coefficients of Self Online dimensions were adequate. Indicators of convergent validity were obtained, finding significant correlations with self-concept, problematic Internet use, and online emotional intelligence. The SO-8 has adequate psychometric properties to be considered a reliable and valid tool to measure the construct of the Self Online in adolescents.
Keywords: self-concept; measurement; validation; gender; gender differences; identity; WOS(2); Scopus